2022
DOI: 10.1002/ijgo.14186
|View full text |Cite
|
Sign up to set email alerts
|

Second stage cesarean section and the risk of preterm birth in subsequent pregnancies

Abstract: Objective To evaluate the risk of spontaneous preterm birth on subsequent pregnancies after second stage cesarean section. Methods This is a retrospective cohort study. Women were included if they had their two consecutive births in Toulouse University Hospital in the study period. The first birth was a singleton livebirth at term (≥37 weeks of gestation), divided in three categories according to the mode of delivery: vaginal delivery (group A), cesarean section before the second stage of labor (group B), cesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies found an association between a second-stage cesarean sections (SS-CSs) and preterm birth (PTB) in the subsequent delivery [5][6][7][8][9][10][11]. This association may be the result of injury to the integrity of the cervix when attempting to extract a low, impacted fetal head during the SSCS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found an association between a second-stage cesarean sections (SS-CSs) and preterm birth (PTB) in the subsequent delivery [5][6][7][8][9][10][11]. This association may be the result of injury to the integrity of the cervix when attempting to extract a low, impacted fetal head during the SSCS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the trend is comparable to outcomes of a systematic review and meta-analysis that focused on the relationship between mode of birth (CS vs. vaginal birth) in the first pregnancy and the risk of subsequent preterm birth. The meta-analysis showed that compared with vaginal birth in the first pregnancy, CS in the first pregnancy increases the risk of preterm birth in subsequent pregnancies [ 12 ], with second stage CS being an independent risk factor for subsequent preterm birth in another study [ 13 ]. It is hypothesized that the uterine structure and/or intrauterine microenvironment may be changed by previous CS, which increases the risk of subsequent preterm birth in the next pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies searched for an association between SSCD and PTB based on the understanding that SSCD is associated with low-segment uterine incisional extension and that uterine extensions can cause mechanical injury to the cervix, possibly leading to cervical incompetence and PTB [3][4][5][6][7]11,16,[18][19][20]. Some found a positive association [4,5,18,19,21] and others did not find an association [7,16,20,22]. Most of these reports studied the association between SSCD and PTB [3][4][5]7,11,18,19] or SSCD and low-segment uterine incision extension [4,20] with only one of these studies combined all three [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some found a positive association [4,5,18,19,21] and others did not find an association [7,16,20,22]. Most of these reports studied the association between SSCD and PTB [3][4][5]7,11,18,19] or SSCD and low-segment uterine incision extension [4,20] with only one of these studies combined all three [16]. Data are presented in Table 7.…”
Section: Discussionmentioning
confidence: 99%